Association between disease activity and clinico-laboratory parameters in Systemic Lupus Erythematosus patients in Hospital Universiti Sains Malaysia: a retrospective study - Mohd Salihin, Nur Aishah Nadirah; Wan Mohamad, Wan Majdiah; Mohamed Thaha, Ummul Aqeela Balqees; Awang Nawi, Mohamad Arif; Che Rahim, Mohd Jazman (IIUM Journal of Orofacial and Health Sciences, 2025)
Systemic Lupus Erythematosus (SLE) is a prototypic autoimmune disease with multi-system involvement. The clinical manifestations and laboratory parameters in SLE patients vary depending upon the disease severity. SLE affects many organs such as skin, brain, and joints, thus affecting the clinical and laboratory parameters of the patients. This study aims to determine the association between the disease activity and clinico-laboratory parameters among SLE patients at Hospital Universiti Sains Malaysia. A total of 32 medical records of SLE patients from 2010 to 2023 were retrieved. The data of clinical and laboratory parameters were obtained and analysed using SPSS 27.0. Demographic data was analysed descriptively, and the Chi square test was used to evaluate the association between SLE disease activity and the clinico-laboratory parameters. We expect the most common symptoms in SLE include arthritis, malar rash, oral ulcer, and increase anti-dsDNA particularly in active SLE. This study showed the most common symptoms were arthritis (n=14;43.8%) followed by oral ulcer (n=10;31.3%). High level of anti-nuclear antibodies (ANA) was found in 21 patients (65.6%) while 18 (56.3%) patients had elevated erythrocyte sedimentation rate (ESR). Sixteen (50.0%) patients demonstrated low serum C3 and C4 levels. Significant associations were found between the disease activity and arthritis (p=0.033), oral ulcer (p=0.002), prolonged fever (p=0.001), ANA level (p=0.009), and anti-dsDNA level (p=0.022). Arthritis was found to be the most frequent symptoms in SLE patients. High level of ANA, increased ESR and low serum complement levels correlates well with active disease. In conclusion, active SLE patients were more frequently presented with arthritis, oral ulcer, prolonged fever, and demonstrated high ANA and anti-dsDNA levels.